Estado nutricional y nivel socioeconómico de los niños en edad escolar del Distrito de Quiruvilca de la Provincia de Santiago de Chuco – La Libertad Noviembre - diciembre 2015 - Cueva Bacilio, Corina Cinthia (2017)
The objective of this study was to evaluate the Nutritional Status and Socioeconomic Level of School - Age Children in the District of Quiruvilca, Province of Santiago de Chuco - La Libertad, November - December 2015. The type of methodology used was cross - sectional descriptive. The sample population consisted of 71 children from 6 to 12 years of age from the only Educational Institutions (Ricardo Palma and Manuel Gonzales Prada), who met the selection criteria, as well as the parents who signed the consent informed. For data collection, the WHO Anthro 2007 score was used and the expression and interpretation of the anthropometric indicators weight / height, height / age, body mass index / age were used. The results indicated that of the total of 71 children in each Educational Institution: Ricardo Palma and Manuel Gonzales Prada, 59.2% and 62.0%, respectively, presented a normal nutritional status, with respect to the T / P indicator (weight for height ); 11.3% and 9.9% were overweight, and 22.5% and 23.9% presented low weight respectively and E / T (height for age), 28.1% and 25, 4% presented a small size, however, 31.0% and 36.7% were within the normal range, and 31.0% and 21.1% were in a high height. Regarding nutritional status, BMI was normal with 57.8% and 64.8%, and underweight the same percentage, 22.5%, while the socioeconomic level was Level II upper low class with 56.3% and 70.4%, respectively. In conclusion according to the three indicators used, the children evaluated have a normal nutritional status with a slight tendency towards low weight and the socioeconomic level that prevails is Level II upper low class